2020
DOI: 10.1111/ijfs.14718
|View full text |Cite
|
Sign up to set email alerts
|

Rye secalin characterisation and use to improve zein‐based film performance

Abstract: Use of rye secalin for preparation of secalin/zein blend film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…The elasticity of film samples including lower whey protein and glycerol contents was not significantly affected by N inclusion; however, the increase in N content resulted in higher E values for higher whey protein and glycerol amounts. Similarly, Qazanfarzadeh and Kadivar demonstrated that whey protein films including a high level of nanocellulose from oat husk (7.5 wt %) resulted in higher elongation at break values due to agglomeration of the fillers. On the other hand, film samples containing higher carrageenan presented higher elasticity when the G/S ratio was increased due to reduced tension of deformation and electrostatic charge.…”
Section: Resultsmentioning
confidence: 99%
“…The elasticity of film samples including lower whey protein and glycerol contents was not significantly affected by N inclusion; however, the increase in N content resulted in higher E values for higher whey protein and glycerol amounts. Similarly, Qazanfarzadeh and Kadivar demonstrated that whey protein films including a high level of nanocellulose from oat husk (7.5 wt %) resulted in higher elongation at break values due to agglomeration of the fillers. On the other hand, film samples containing higher carrageenan presented higher elasticity when the G/S ratio was increased due to reduced tension of deformation and electrostatic charge.…”
Section: Resultsmentioning
confidence: 99%
“…Tukey test was used to compare the mean at a 95% confidence level. Figure 1 shows that the extracted SCL exhibited the well-known protein electrophoretic profile containing four fractions (HMW, γ-75 KDa, ω, and γ-45 KDa) [4]. It is well known that all nucleophilic groups of protein amino acid residues, such as amino, hydroxyl, sulfhydryl, and phenol groups, can be acylated by fatty acid chlorides [25].…”
Section: Discussionmentioning
confidence: 98%
“…However, prolamin occurring in rye grains, and alcohol-soluble protein fraction called secalin (SCL), has not been so widely studied up to now, in relation to its functionality in food systems, as wheat prolamin has been. According to previous studies, the electrophoretic pattern of SCL shows four groups of polypeptides, indicated as high molecular weight (HMW, >100 KDa), γ-75 KDa, ω (50 KDa), and γ-40 KDa proteins, respectively [ 4 ]. Moreover, quantitative amino acid analysis evinced that glutamic acid and proline are the predominant components in SCL, followed by leucine, phenylalanine, and serine [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations